Movement sensor faucet/ Muhammad Idham Kamarulzaman, Zulhanif Rozali and Muhammad Iqmal Rosely - Kamarulzaman, Muhammad Idham; Rozali, Zulhanif; Rosely, Muhammad Iqmal (2018)
The goal of this project was to decrease the amount of water waste inside the campus as students tends to forget to close the tap and cause water waste inside the campus. The design stabilizes soap, water, and energy costs and has a unit cost comparable to current public facilities components. Then, a prototype was created with an electrical control circuit and viable mechanical design to prove the validity of the idea. The prototype was meant to replicate a unit that washed a user’s hands in a consistent manner. The prototype used simpler, less expensive components to dispense soap and wash the hands. Due to a lack of custom parts, the prototype required the user to rub their hands together to work the soap into their hands and allow the water to fully rinse the soap off. The prototype functioned without requiring the user to touch anything to operate the device. This touch free operation was accomplished with an ultrasonic sensor and coded Arduino UNO that began the process of washing hands once the beam was interrupted.